(untitled) (Revista do Centro de Estudos Portugueses, 2008)
Esse artigo apresenta os contrastes entre as obras de Lúcio Cardoso e as de Cornélio Penna, acompanhando o desenvolvimento de seus escritos e destacando suas características fundamentais. This article presents the contrasts between the works of Lúcio Cardoso and those of Cornélio Penna, accompanying the development of his written ones and detaching his basic characteristics.